A decoupling control of composite cage rotor bearingless induction motor based on SA‐PSO support vector machine inverse. (28th June 2021) - Lu, Chengling; Yang, Zebin; Sun, Xiaodong; Ding, Qifeng; Zhao, Qian
Summary: A composite cage rotor bearingless induction motor (CCR‐BIM) is a complicated system with multi‐variable, nonlinear, and strong coupling. The decoupling control among speed and flux linkage and radial displacement is the base of the stable operation based on the structure, the suspension force and the mathematical model of the CCR‐BIM. A decoupling control strategy based on simulated annealing particle swarm optimization (SA‐PSO) support vector machine (SVM) inverse is proposed for the CCR‐BIM. First, the state equation and reversibility of the system are analyzed using a CCR‐BIM mathematical model and a compounded pseudo‐linear system consisting of the inverse system constructed is decoupled into two displacement subsystems by nonlinear SVM in series with the original system, a speed subsystem, and a flux linkage subsystem. Second, the SA‐PSO is introduced to improve the precision of the prediction model. Finally, results of simulation and experimental verify that the proposed strategy not only achieves the decoupling control between the speed, radial displacement and flux linkage, but also achieves stable suspension and high performance of the CCR‐BIM. Abstract : According to electromagnetic field theory, when the current I 1 is separately injected into the torque winding, it generates symmetric two‐pole flux linkage ψ 1 ; when the current I 2 is separately injected into the torque winding, it generates symmetric four‐pole flux linkage ψ 2 . When the two currents I 1 and I 2 are injected at the same time, air‐gap magnetic density distribution is unbalanced and the suspension force Fy along the y ‐axis positive direction can be generated. Therefore, by changing the direction and magnitude of the two currents of two windings in the CCR‐BIM, radial suspension force in any direction can be generated. The principle of radial suspension force is shown in Figure 3. The principle of electromagnetic torque in the CCR‐BIM is similar to induction motor, both of them are based on the Lorentz force.